Structural and dimensional analysis of personality in healthy older adults - Silvia Gobbo; Elena Trapattoni; Daniele Romano (Scientific Reports)
Abstract Ageing is a complex process involving physical, cognitive, and social changes. Despite these transformations, research on personality development remains limited. Traditional models propose that personality remains stable beyond early adulthood; however, age-related changes in other areas suggest potential structural reorganization. This study investigates whether aging leads to both dimensional and structural changes in personality, exploring how personality traits evolve and reorganize in later life. We conducted an online study with 376 retired adults over 65, who completed two personality questionnaires, a set of behavioral criteria, and a well-being questionnaire. Our findings show that the HEXACO Adjectives Scale (HAS) captures age-related personality changes, with higher Honesty-Humility, Extraversion, and Agreeableness, lower Emotionality, and stable Openness. We employed Exploratory Graph Analysis (EGA) to examine personality structure, offering a novel perspective on age-related changes. EGA revealed partial reorganization of the HEXACO model. Honesty-Humility and Agreeableness adjectives shuffled and merged into two distinct communities based on valence, reflecting a positive bias associated with ageing. This change, alongside increased Honesty-Humility, suggests growing emphasis on self-perception shaped by social context in later life. These findings challenge traditional views of personality stability in older adulthood, highlighting the dynamic nature of personality and ageing.